Disparate Racial Impacts of Shelby County v. Holder on Voter Turnout - Stephen B. Billings; Noah Braun; Daniel Jones; Ying Shi (Institute of Labor Economics (IZA), 2022)
In Shelby County v. Holder (2013), the Supreme Court struck down a core provision of the Voting Rights Act (VRA) that enabled federal electoral oversight in select jurisdictions. We study whether this decision disproportionately impacted ballot access for Black and Hispanic registered voters. We use a rich dataset on voter behavior for the universe of registered voters combined with Census block-level sociodemographic attributes to document a decrease in turnout for Black, relative to white, individuals. These effects are concentrated in counties with larger Black and Hispanic populations, consistent with strategic targeting of voter suppression.
Keywords: D72; J15; K16; 330; Voting Rights Act; political participation